Marine Smenospongia extract mitigated co-infection with Trichodina sp. and Flavobacterium columnare in Nile tilapia: insights into promoting growth performance, immune, antioxidant and autophagy defenses, and suppression of endoplasmic reticulum stress-related genes - Ibrahim, Doaa; Pet, Ioan; Anter, Reham G. A.; Abdelwarith, Abdelwahab A.; Rahman, Mona Mohammed I. Abdel; Shafik, Basant M.; Younis, Elsayed M.; Basiony, Asmaa; Atwa, Shimaa A. E.; Metwally, Aya Sh.; Tolba, Heba A.; Ahmadi, Mirela; et al. (Frontiers in Marine Science, 2024)
Imperative to identify novel natural sources from marine environment with unique immunomodulatory and antioxidant efficacy is a point of interest in intensive fish farming. In this sense, marine sponge extract derived from Smenospongia (SS-extract) was tested for its potential antiinflammatory, antioxidant and antimicrobial activities during the concurrent infection with Trichodina sp and Flavobacterium columnare in Nile tilapia. A total of 625 Nile tilapia fingerlings were distributed into five groups: control group (with no additives) and four groups fed control diet fortified with SS-extract at the level of (50, 100, 150 and 200mg/kg) for 60 days. The parasitic challenge with Trichodina sp was done at the end point of feeding trial and at 7 days post infection (dpi), fish were coinfected by F. columnare. Significant improvement in Nile tilapia growth related parameters was detected in groups received SS-extract at the levels of 150 and 200 mg/kg. Scavenging ability for free radicals (ABTS and DPPH) was maximized with higher SS-extract supplemental levels. Simultaneously, the antioxidant defense of Nile tilapia fed 150 and 200 mg/kg was augmented with a contrary decline in oxidative associated indicators (reactive oxygen species: ROS, hydrogen peroxide: H2O2, and Malondialdehyde: MDA). Feeding on higher concentrations of SS-Extract potentiated the immune response of Nile tilapia before infection and even after coinfection which parallel with subsiding the exaggerated inflammatory response after concurrent infection. Concurrently, mRNA expression of autophagy-encountered genes (Atg5 and 12, LC3-II and BCLN1) showed their highest expression in 200 mg/kg diet with lowest expression of mTOR gene. The infection intensity and rate and mucous score were displayed their lowest levels in 200 mg/kg SS-extract at 20 dpi. Interestingly, higher levels of SS-extract triggered the antimicrobial peptides (upregulation of Hepcidin and βdefensin-1). In contrast excessive expression of endoplasmic reticulum genes (atf4, JAK1, PERK and eif2α) in control infected group was downregulated in 200 mg/kg SS-extract. The quantification of F. columnare indicated that the columnaris coinfection severity displayed its lowest rate in 200 mg/kg SS-Extract supplemental group. Collectively, strategic siting based on fortification Nile tilapia's diet with SS-extract was elucidated to reinforce its immune and antioxidant defense during the concurrent infection.